Comparative Analysis of Radix Sort, Quick Sort, and Bubble Sort Algorithms in Data Sorting Based on Array Size and Time - Kurnia Wati Fadhillah; Nandy Thaher Ulga; Raffi Ramadhan Oktaviansyah; Farah Sulistia; Jeni Amanda; Akhmad Jayadi (Al'Adzkiya, 2025)
An algorithm is a series of logical actions used to solve important problems in contemporary programming and data processing. The purpose of this study is to compare the time efficiency of three sorting algorithms: Bubble Sort, Radix Sort, and Quick Sort. All algorithms are used on small (10-100 elements), medium (1,000-10,000 elements), and large (more than 100,000 elements) arrays, with execution time using Java. The results show that Radix Sort and Quick Sort are generally more efficient and scalable than Bubble Sort, especially for large arrays and random or semi-sorted data. Radix Sort excels on small and medium arrays under various conditions, while Quick Sort excels on large arrays in the average and nearly sorted cases. Although Bubble Sort can be the fastest in the best case for large arrays, its performance drops drastically in the average and nearly sorted cases. In conclusion, the selection of the best sorting algorithm depends heavily on the type of input data, such as its size and the degree of initial sorting.